ANALISIS PENDAPATAN ASLI DAERAH KABUPATEN KUTAI TIMUR - Titin Ruliana, Suzanty Usman¹, Elfreda Aplonia Lau² (EKONOMIA, 2016)
Enabling Autonomy, according to Law No. 32 of 2004, local autonomy rights, authorities, and obligations of autonomous regions to set up and manage their own affairs and interests of local communities in accordance with the regulations, undangan.Pendapatan (PAD) is the income collected Regional Regional Regulation in accordance by legislation No. 34 Year 2000 revenue (PAD) sourced from Local Taxes, Levies, the results of which are separated regional wealth management, and other legitimate PAD (includes proceeds from the sale of regional assets are not separated, current accounts, interest income, exchange gain the rupiah against foreign currencies and commissions, discounts, or other forms as a result of the sale and or procurement of goods or services by Regions). Based on the background that has been described previously, the research problems can be formulated as follows:1. Is Local Tax contributes very well to the East Kutai Regency PAD for 2009, 2010, 2011, 2012 and 2013?2. Do Levies contributed very well to the PAD Kutai Timuruntuk 2009, 2010, 2011, 2012 and 2013?3. Is the Company's Profit Regions contribute very well to the PAD Kutai Timuruntuk 2009, 2010, 2011, 2012 and 2013?4. Are Other legitimate PAD contribute very well to the PAD Kutai Timuruntuk 2009, 2010, 2011, 2012 and 2013?5. Are Taxes East Kutai Regency very efektifuntuk 2009, 2010, 2011, 2012 and 2013?6. Do Levies East Kutai very efektifuntuk 2009, 2010, 2011, 2012 and 2013?7. Does the Company's Profit East Kutai Regency very efektifuntuk 2009, 2010, 2011, 2012 and 2013?8. Are Other legitimate PAD East Kutai very efektifuntuk 2009, 2010, 2011, 2012 and 2013?The main theory used in this research is the management keuangan.Alat analysis used in this research is the analysis of the contribution and effectiveness ratio analysis.The results of this study indicate that the contribution of local taxes, levies, profit regional companies and others local revenues legitimate, after doing the testing concluded in general the contribution rate of local taxes, levies, profit regional companies, and others eligible PAD does not reach the level very good category. Unless the contribution rate deodorized legitimate PAD in 2009 to reach the very good category. The effectiveness of local taxes, levies, profit regional companies, and others of local revenue legitimate, once categorized in the criteria for effectiveness set by the Ministry, it can be concluded that the overall level of effectiveness in the category very effective for local taxes, levies and others PAD legitimate